Risk Factors for Stunting in Toddlers Aged 24-59 Months with Stunting Events in Padang Village Manggeng District of Southwest Aceh Regency - Zakiyuddin, Zakiyuddin; Yarmaliza, Yarmaliza; Fitriani, Fitriani; Reynaldi, Fitrah; Farisni, Teungku Nih; Desi Arisandi, Dedi; Gunawan, Gunawan; Nurdin, Ambia; Putro, Wahyu Gito (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2023)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition. This study aimed to see whether there is a definite relationship between maternal height, maternal education, maternal nutrition knowledge, maternal age, and maternal employment status against stunting cases in Manggeng village, Southwest Aceh Regency. Research is an observational analysis with a cross-sectional approach. They were held for two months (November September 2021) in Padang village Manggeng district of Southwest Aceh Regency. The sample withdrawal was a saturated sample of 45 mothers with toddlers ages 24-59. The results of the analysis concluded that there was no meaningful relationship between the characteristics of the mother of toddlers (height, age, education level, knowledge of nutrition, and employment status) or stunting factors that were examined against the number of stunting cases in Padang village which means the variables used statistically less precisely as variables predicator stunting rate. The level of risk of observed factors consisting of maternal height means that Stunting tendencies are riskier in mothers with short size than mothers with a high body, as well as the risk factors of the education level, Knowledge and status of the mother's work.